Simulation of Planetary Gearbox - Maria Tomasikova; Tomas Gajdosik; Michal Lukac; Frantisek Brumercik (Communications - Scientific letters of the University of Zilina, 2017)
This article is about calculation of planetary gearbox. The gearbox consists of two planetary gears - input and output. The gearbox model is created in Simscape Driveline. The model contains Simscape blocks which represent a gear box, clutch, ideal torque source and many others blocks. At the end we compare our results of simulation with calculations.